Improved room temperature ionic conductivity of Ta and Ca doped Li7La3Zr2O12 via a modified solution method - Chen, Xiaolan; Cao, Tianxiang; Xue, Mingzhe; Lv, Hong; Li, Bing; Zhang, Cunman (Solid state ionics, 2018)
Ta and Ca doped Li7La3Zr2O12 is synthesized via a modified solution method without producing toxic NOx. Li7−x+yCayLa3-yZr2−xTaxO12 series with x range from 0 to 2 and y range from 0 to 0.05 are prepared and their ionic conductivities are found to be greatly enhanced by doping Ta and Ca to a certain amount. The optimized amount of Ta doped in Li7−xLa3Zr2−xTaxO12 is found to be x=0.6, corresponding to a total ionic conductivity of 1.95×10−4Scm−1. When further doped with Ca, a synergetic effect from Ta and Ca is observed and a high ionic conductivity of 2.84×10−4Scm−1 is achieved in Li6.45Ca0.05La2.95Ta0.6Zr1.4O12. The simple solution method proposed in this work is considered to be potentially applied as a general methodology for synthesizing metal doped Li7La3Zr2O12. •A modified solution method was developed to synthesize Ta and Ca substituted Li7La3Zr2O12 (LLZO).•None toxic NOx was produced during synthesis process.•The optimized amount of Ta doped in Li7−xLa3Zr2−xTaxO12 is found to be x=0.6.•Ta and Ca exhibits synergistic effect on the ionic conductivity of LLZO.•High ionic conductivity of 2.84×10−4Scm−1 was achieved from Li6.45Ca0.05La2.95Ta0.6Zr1.4O12.